Noted: Modern activist journalism - Steve Ellmers (Asia Pacific Network, 2014)
Review of: Censored 2014: Fearless Speech in Fateful Times, by Mickey Huff and Andy Lee Roth with Project Censored. New York: Seven Stories Press, 2013, 431pp. ISBN 978-1-60980-484-7